Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $z=f(x,y)$, then total derivative is $\mathrm{d}z=\frac{\partial f}{\partial x}\mathrm{d}x+\frac{\partial f}{\partial y}\mathrm{d}y$. If $\mathrm{d} z=0$, how do you show that $z$ is a constant?

share|cite|improve this question
up vote 3 down vote accepted

Since $dz=0$, $\frac{\partial z}{\partial x} = \frac{\partial z}{\partial y}=0$. Hence, on the one hand $z(x,y)=f(y)$ and on the other $z(x,y)=g(x)$ by integrating. So $f(y)=g(x)$. Differentiating both sides with respect to $x$, we have $0=\frac{\partial g}{\partial x}$. Therefore $z(x,y)=g(x)=C$.

share|cite|improve this answer
Great! that is done solving dz as an exact differential equation. Arriving at f(y)=g(x) is enough to conclude z=f(y)=g(x)=C since any expression on x alone, equal to another on y alone, can only be a constant to be well-defined. – Javier Álvarez Feb 22 '11 at 1:22
Right. Specifically, $g(x)-g(x_0)=f(y)-f(y)=0$ for any $x,x_0, y$. So $g(x)=g(x_0)$. – AppliedSide Feb 22 '11 at 1:40

If $df = 0$, then $\frac{\partial f}{\partial x} \ dx = -\frac{\partial f}{\partial y} \ dy$. I guess one could solve for $f(x,y)$ to get $f(x,y) = g(x-y)$ since $(f_x+f_y)g(x-y) = g'(x-y)+(-1)g'(x-y) = 0$ identically for some $g \in C^1$.

share|cite|improve this answer
Thanks. I already know this but how does this help to show that $z$ is constant? – Vafa Khalighi Feb 21 '11 at 22:14

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.